2004
DOI: 10.1128/jcm.42.11.5324-5326.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Leukotoxin-Producing Staphylococcus intermedius in Isolates from Dogs and Pigeons

Abstract: Staphylococcus intermedius isolates from dogs (n ‫؍‬ 44) and pigeons (n ‫؍‬ 62) were categorized into 12 types by intergenic ribosomal DNA spacer polymorphism analysis. All isolates from pigeons were lukS positive and all isolates from dogs were lukS and lukF positive by dot blot analysis. The mean leukotoxicity titer for dog isolates was at least 129-fold higher than that for pigeon isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 17 publications
(16 reference statements)
3
54
1
4
Order By: Relevance
“…The high prevalence of genes Luk S-I (95%), Luk F-I (91%), and SIET (91%) observed in this study is similar to the data from other studies, where 98%, 100%, and 100% of canine isolates were found to be positive for these genes [15,[22][23][24][25]. This high prevalence probably indicates their importance for active infection.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The high prevalence of genes Luk S-I (95%), Luk F-I (91%), and SIET (91%) observed in this study is similar to the data from other studies, where 98%, 100%, and 100% of canine isolates were found to be positive for these genes [15,[22][23][24][25]. This high prevalence probably indicates their importance for active infection.…”
Section: Discussionsupporting
confidence: 81%
“…In present study, we observed higher prevalence compared and only hlg ƴ gene showed low frequency [15,[21][22][23]. These discrepancies may be due to the differences in the health status of the animals between studies or due to considerable genetic variability among the isolates; for example, gene sea is more prevalent in pyoderma isolates than those present on healthy skin.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…delphini was initially isolated from a purulent skin lesions in dolphins (Voraldo et al 1988). Subsequently, this species was also found in a wide range of animals, including horses, mink, domestic pigeons, and recently it was isolated from donkeys (Hesselbarth and Schwarz 1995, Futagawa-Saito et al 2006, Futagawa-Saito et al 2007, Sledge et al 2010, Gharsa et al 2014. The phylogenetic analysis of nuc gene sequences revealed, that this species is formed by two genetically distinct groups (A and B) (Sasaki et al 2007).…”
mentioning
confidence: 99%
“…coagulans, and also coagulasenegative Staphylococcus spp. (CoNS), are implicated in the etiology of animal diseases, such as suppurative disease, mastitis, arthritis and urinary tract infection, due to their virulence factors (Futagawa-Saito et al, 2006;Silva et al, 2003). Staphylococcus species are usually resistant to ß-lactams, aminoglycosides and macrolides.…”
mentioning
confidence: 99%